Response to: USP26 regulates TGF‐β signalling by deubiquitinating and stabilizing SMAD7; not applicable in glioblastoma. (20th December 2019) - Kit Leng Lui, Sarah; Iyengar, Prasanna Vasudevan; Jaynes, Patrick; Isa, Zul Fazreen Bin Adam; Pang, Brendan; Tan, Tuan Zea; Eichhorn, Pieter Johan Adam
Abstract : The response by the authors.